Hubungan Tingkat Pendidikan dengan Partisipasi Masyarakat pada Bank Sampah di Wilayah Kecamatan Kemayoran - Amalia Dinianti (Edukasi IPS, 2019)
This study is aims to find out the relationship between The Level of Education towards Public Participation at Waste Bank in The Subdistrict Area of Kemayoran. This study was quantitative research. The population were 134 participants of the waste bank in The Subdistrict Area of Kemayoran. The sample was 100 participants. The research sampling techniques were Slovin and Proportional Stratified Sampling. Proportional Stratified Sampling was according to the level of education of people who participated on waste bank. Data collection technique was done by using a questionnaire. The data analysis technique was done by multiple linear analysis. The result shows that there is a significant relationship between The Level of Education towards Public Participation at Waste Bank in The Subdistrict Area of Kemayoran, the result is 0,315 and the determinant coefficient (r2) is 0,099 or 9,9% in percentage. The result means that the level of education only contributes 9,9% as the factor of Public Participation at Waste Bank in The Subdistrict Area of Kemayoran. There are four more factors such as knowledge and skill, gender, types of occupation, and belief of the certain culture which can contribute another 90,1% to Public Participation at Waste Bank in The Subdistrict Area of Kemayoran. This study can be used as the reference for the next study that relates to social and environmental science. Keywords: Level of Education, Public Participation